Análise do processo trabalho-saúde-doença dos profissionais que atuam em hospitais oncológicos - Santos, Maria Tamires Fernandes dos (2021)
This dissertation has the general objective of analyzing the work-health-disease process of professionals who work in oncology hospitals. For that, the theoretical contribution of the psychodynamics of work was used to discuss the aspects that emerged in the research. Seventeen health professionals who work in oncology hospitals in the State of Paraíba-PB participated in this study. They answered a sociodemographic questionnaire and a semistructured interview conducted by video conference due to the Pandemic by Covid-19. For the analysis of the questionnaire data, a basic descriptive analysis was made and for the treatment of the interview materials, we used the lexical analysis software IRAMUTEQ (Interface of R pour les Analyzes Multidimensionnelles de Textes et de Questionnaires). The results will be presented in two articles. The first article is intended to analyze the sources of pleasure and suffering of professionals working in oncology hospitals. It addresses issues such as working conditions, health implications of work, pleasure at work, and suffering at work, as well as the defensive strategies used by these workers in the search for psychic balance. The second article explores the cooperation in the work of these cancer professionals, addressing issues such as the experience of practice, deontic activity, trust, and the dynamics of recognition at work. Finally, it is hoped that this study can contribute to discussions that enable changes in work, especially in what was identified as harmful by the interviewees and that reinforces the actions that promote the health of health professionals working in oncology.